Gastrointestinal dysmotility: A qualitative exploration of the journey from symptom onset to diagnosis. Issue 8 (25th March 2018) - Twist, K.; Ablett, J.; Wearden, A.; Paine, P.; Vasant, D.; Lal, S.; Peters, S.
Abstract: Background: Gastrointestinal dysmotility (GID) covers a spectrum of disorders disrupting enteric neuromuscular co‐ordination which, when severe, causes intractable gastrointestinal symptoms and malnutrition and is a recognized cause of chronic intestinal failure. To date, no study has provided an in‐depth account of the experiences of patients with severe GID and their psychosocial needs. This study aimed to explore patients' experiences from symptom onset and the process of seeking and receiving a diagnosis. It specifically explored the psychological effect of this process and the effect on relationships. Methods: Participants (n = 20, mean age = 47.9, female n = 16, parenteral nutrition = 13) were recruited from a UK center with tertiary Neurogastroenterology and Intestinal Failure services. A qualitative exploratory design with semi‐structured in‐depth interviews was used. Data were analyzed using thematic analysis. Key Results: Significant delays were experienced in obtaining a diagnosis. Participants reported having their mental health questioned and felt that they had to fight to prove their symptoms had a physical basis to access appropriate treatment. Although a diagnosis helped legitimize symptoms, the condition remained poorly understood by participants themselves, relatives, and health professionals. Participants discussed the impact that "feeling delegitimized" and the "lack of coherent understanding of GID" had on their relationships and mental health. Conclusions & Inferences: The distressing experience of GID symptoms are compounded by a delay in validating symptoms and lack of coherent understanding. More knowledge of GID is needed by health professionals to speed up diagnosis and offer more coherent information. The psychological impact of a GID diagnosis should be acknowledged early to help facilitate adjustment. Abstract : The manuscript is an empirical paper conducted with people diagnosed with severe gastro‐intestinal dysmotility (GID). It aimed to explore patients' experiences from symptom onset and the process of seeking and receiving a diagnosis. The distressing experience of GID symptoms is compounded by a delay in validating symptoms and lack of coherent understanding. More knowledge of GID is needed by health professionals to speed up diagnosis and offer more comprehensible information. The psychological impact of a GID diagnosis should be acknowledged early to help facilitate adjustment. Clinical implications and recommendations for future research are discussed.